Cost-effectiveness and cost-utility of hypertension and hyperlipidemia collaborative management between pharmacies and primary care in portugal alongside a trial compared with usual care (USFarmácia®) - Costa, Suzete; Guerreiro, José; Teixeira, Inês; Helling, Dennis K.; Pereira, João; Mateus, Céu (Frontiers in Pharmacology, 2022)
Background: There is little experience in the economic evaluation of pharmacy/ primary care collaborative health interventions using interprofessional technology-driven communication under real-world conditions. This study aimed to conduct cost-effectiveness and cost-utility analyses of a collaborative care intervention in hypertension and hyperlipidemia management between pharmacies and primary care versus usual (fragmented) care alongside a trial. Methods: An economic evaluation was conducted alongside a 6-month pragmatic quasi-experimental controlled trial. Data sources included: primary care clinical software; pharmacy dispensing software; patient telephone surveys; and published literature. The target population was adult patients on hypertension and/or lipid-lowering medication. The perspective was societal. We collected patient-level data on resource use to estimate trial costs. Effect outcomes included blood pressure (BP) and quality-adjusted life years (QALYs). Bootstrapping was used to estimate uncertainty around the incremental cost-effectiveness and cost-utility ratios. Cost-effectiveness planes and acceptability curves were estimated. Results: The intervention was not shown to have reasonable levels of cost-effectiveness or cost-utility when compared to usual care, as denoted by the levels of uncertainty expressed in wide confidence intervals. The probability for the intervention to be cost-effective is 28% at the threshold of €20,000 per QALY gained and 57% at the threshold of €500 per mmHg systolic BP decrease. Conclusions: Considering the limitations of the trial which affected effectiveness and economic outcomes our results are not generalizable for community pharmacy and primary care in Portugal. This research offers, however, valuable lessons on methods and strategies that can be used in future economic evaluations of collaborative public health interventions with the potential for reimbursement. Trial Registration: Current Controlled Trials (ISRCTN): ISRCTN13410498, retrospectively registered on 12 December 2018: https://www.isrctn.com/ISRCTN13410498